Autosomal dominant cortical myoclonus and epilepsy (ADCME) with complex partial and generalized seizures: A newly recognized epilepsy syndrome with linkage to chromosome 2p11.1-q12.2. - Guerrini, R; Bonanni, P; Patrignani, A; Brown, P; Parmeggiani, L; Grosse, P; Brovedani, P; Moro, F; Aridon, P; Carrozzo, R; Casari, G (2001)
We describe a pedigree in which eight individuals presented with a non-progressive disorder with onset between the ages of 12 and 50 years. It was characterized by predominantly distal, semi-continuous rhythmic myoclonus (all patients), generalized tonic-clonic seizures (all patients) and complex partial seizures (three patients). Most individuals had rarely suffered seizures and had a normal cognitive level, but three individuals with intractable seizures had mild mental retardation. The pattern of inheritance was autosomal dominant with high penetrance. We defined this disorder as autosomal dominant cortical myoclonus and epilepsy (ADCME). All patients had frontotemporal as well as generalized interictal EEG abnormalities. A neurophysiological study of the myoclonus suggested a cortical origin. Back-averaging of the data generated a series of waves with a frequency that mirrored the frequency of EMG bursts. Frequency analysis identified significant peaks with coherence between EMG and EEG, which were recorded over the contralateral rolandic area in five patients. The frequency of coherence was 8-25 Hz and phase spectra confirmed that EEG activity preceded EMG activity by 8-15 ms. In two individuals there was also significant coherence between the ipsilateral EEG and EMG, consistent with the transcallosal spread of myoclonic activity. The C-reflex at rest was enhanced and somatosensory and visual evoked potentials were of high amplitude. The resting motor threshold intensity to transcranial magnetic stimulation was significantly reduced (38%; SD +/- 7; P = 0.01) and the post-motor evoked potential silent period (101 ms; SEM +/- 10) was significantly shortened compared with the controls (137 ms; SEM +/- 18). These clinical and neuro- physiological characteristics suggest diffuse cortical hyperexcitability and high propensity for intra-hemispheric and inter-hemispheric cortical spread, as well as rhythmic myoclonic activity. Genome-wide linkage analysis identified a critical region spanning 12.4 cM between markers D2S2161 and D2S1897 in 2p11.1-q12.2, with a maximum two-point LOD score of 3.46 at Theta 0.0 for marker D2S2175. Multipoint LOD score values, reaching 3.74 around D2S2175, localize the ADCME gene to the centromeric region of chromosome 2. The exclusion of the locus for familial adult myoclonic epilepsy on chromosome 8q23.3-q24 from linkage to our family and the new localization of the responsible gene to chromosome 2cen, together with the different phenotype, define a new epilepsy syndrome. We hypothesize that the responsible gene causes cortical hyperexcitability that is widespread but particularly involves the frontotemporal circuits.